Back Cover: Defect‐Free Alternating Conjugated Polymers Enabled by Room‐ Temperature Stille Polymerization (Angew. Chem. Int. Ed. 16/2022). Issue 16 (19th March 2022) - Ma, Bowei; Shi, Qinqin; Ma, Xiaoying; Li, Yawen; Chen, Hao; Wen, Kaikai; Zhao, Ruihua; Zhang, Fengjiao; Lin, Yuze; Wang, Zhixiang; Huang, Hui
Abstract : Defect‐free alternating conjugated polymers were produced by exploring palladium‐catalyzed Stille polymerization at room temperature. The selected copolymers demonstrated no homocoupling defects and superior charge transport properties, thus paving the road for the development of plastic electronics. Details of this study are reported by Qinqin Shi, Hui Huang, and co‐workers in their Research Article (e202115969) .